2013
DOI: 10.3141/2326-03
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Sensitivity of Transportation Assets to Extreme Weather Events and Climate Change

Abstract: Transportation officials are increasingly faced with challenging decisions about how to design, plan, and manage infrastructure to confront changes in climate and extreme weather events. An understanding of which impacts affect infrastructure and at what point damage begins to occur is a critical step toward assessing overall vulnerability and risk. However, few resources exist to help managers and designers identify key thresholds and indicators of sensitivity to weather and climate impacts. This paper introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Similarly, a decreasing effect of adverse climate (temperature inversion index) was identified in the transportation system. According to the literature, traffic flow and roads are usually sensitive to adverse variables of climatic conditions (Reed et al 2010;Rowan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a decreasing effect of adverse climate (temperature inversion index) was identified in the transportation system. According to the literature, traffic flow and roads are usually sensitive to adverse variables of climatic conditions (Reed et al 2010;Rowan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tailoring sensitivity matrices to individual regions could help transportation planners screen for especially sensitive assets and services (Rowan et al 2013). Similarly, decision-support tools could help agencies target the most vulnerable places and structures, diverting funding to those projects that are most critical for resilience (Croope and McNeil 2011).…”
Section: Resourcesmentioning
confidence: 99%
“…These secondary impacts make the entire environment, including marginal platforms and access to offshore, dangerous to operate. A scoping investigation of the research area showed that tropical storms, lightning, and thunderstorms are also on the increase in the region, widening the index of vulnerability (Rowan et al 2013). The investigation revealed that the impact of thunderstorms and regular lightening charges on metallic systems have been reported as a potential for fire ignition and combustion and, hence, constitutes a very high risk for oil/gas field installations.…”
Section: Introductionmentioning
confidence: 99%